ANALISIS PERTUMBUHAN UNIT USAHA SYARIAH BANK PEMBANGUNAN DAERAH JAMBI - Najmah Fatin; Hansen Ruslian; Ahmad Syahrizal (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2022)
This thesis aims to determine the growth of the Sharia Business Unit of the Jambi Regional Development Bank as seen from the development of assets, financing and profit for the current year. In this study using a qualitative descriptive method of collecting data by conducting observations, interviews and documentation. While the data analysis method used in this writing is descriptive analysis. In this thesis, the author concludes that the growth in the sharia business unit of the Jambi Regional Development Bank has been stable and increased significantly, the Jambi Regional Development Bank Sharia Business Unit or known as Jambi Sharia Bank is at a stable point in running the company's operations. Significant and continues to increase every year. In its growth, banks have factors that affect the growth of assets, financing and also profits such as the amount of TPF, the level of profit sharing and so on.